DIMENSIONS ASSOCIATED WITH BURNOUT SYNDROME IN TEACHERS: A CRITICAL ANALYSIS - Moreira, Kellen Campos Castro (2020)
Burnout Syndrome can be defined as exhaustion, whose education professionals are among the most affected category. This article aimed to analyze the dimensions associated with Burnout Syndrome in teachers, from a public school, in a city located in Minas Gerais. Data collection occurred through the application of a questionnaire, which were analyzed by the dimensions: Emotional Exhaustion, Depersonalization and Personal Achievement at Work. Among the results, the most marked items are according to the dimensions: I feel that through my work I positively influence the lives of others, I feel exhausted at the end of a working day, I have become more insensitive with people. Teachers are strongly committed to the profession, as evidenced in the Personal Achievement at Work dimension. However, they are faced with conditions that are not always favorable for work resulting in Emotional Exhaustion. In addition to daily coexistence and involvement with the community, they end up exacerbating wear and tear and developing a protection mechanism, Depersonalization. It is known that the Burnout Syndrome can generate, in addition to loss of quality of life of teachers, in pedagogical implications. The limitations of this study are recognized and more research and efforts are suggested to improve working conditions (physical structure, salary, workload) and mental health, with spaces to share the anxieties, challenges and achievements of teachers at school.